Electrochemical behaviour of passivation film formed on SLM-fabricated Hastelloy X superalloy surface in 10 wt% NaNO3 solution. (September 2022) - Yin, Yingyue; Li, Huixiang; Pan, Shuaihang; Zhang, Jianhua; Han, Quanquan; Yang, Shengzhao
Abstract: Understanding passivation behaviour of Hastelloy X (HX) superalloy by selective laser melting (SLM) is important to its anti-corrosion applications. The configuration, electronic properties, and electrochemical performance of passivation film on SLM-fabricated HX alloy surface were systematically compared with commercial wrought counterpart. The results indicated a thicker and more compact passivation film on the XOY surface (perpendicular to build direction) was attributed to its finer grains and higher density of low angle grain boundaries (LAGBs). These active sites increased the film growth rate by decreasing oxygen vacancy mobility in instantaneous nucleation process, leading to a superior corrosion resistance than wrought counterparts. Highlights: The electrochemical behaviour of passivation film on SLM-fabricated Hastelloy X (HX) was investigated. The SLM-fabricated HX surface formed a thicker and more compact passivation film with lower vacancy diffusion coefficient. The refined grain size and a high density of low angle grain boundaries in SLM-fabricated HX contributed to this trend. The SLMed XOY surface of HX alloy had the supreme corrosion resistance.